Interrupted Baeyer–Villiger Rearrangement: Building A Stereoelectronic Trap for the Criegee Intermediate - Vil', Vera A.; dos Passos Gomes, Gabriel; Bityukov, Oleg V.; Lyssenko, Konstantin A.; Nikishin, Gennady I.; Alabugin, Igor V.; Terent'ev, Alexander O. (Angewandte Chemie International Edition, 2018)
The instability of hydroxy peroxyesters, the elusive Criegee intermediates of the Baeyer–Villiger rearrangement, can be alleviated by selective deactivation of the stereoelectronic effects that promote the 1,2‐alkyl shift. Stable cyclic Criegee intermediates constrained within a five‐membered ring can be prepared by mild reduction of the respective hydroperoxy peroxyesters (β‐hydroperoxy‐β‐peroxylactones) which were formed in high yields in reaction of β‐ketoesters with BF3⋅Et2O/H2O2. No longer elusive: The instability of hydroxy peroxyesters, the elusive Criegee intermediates of the Baeyer–Villiger rearrangement, can be alleviated by selective deactivation of the primary and secondary stereoelectronic effects that promote the 1,2‐alkyl shift. Stable cyclic Criegee intermediates constrained within a five‐membered ring can be prepared by mild reduction of the respective hydroperoxy peroxyesters.